ANALISIS KECANDUAN GADGET PADA ANAK USIA SEKOLAH DASAR DI TULANGAN - Anggita, Nancy; Haryanto, Budi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the forms, levels, and impacts of gadget addiction among elementary school children in Tulangan, Sidoarjo. The increasing use of gadgets, which initially functioned as learning and entertainment tools, has developed into a source of dependency affecting children’s psychological, social, academic, and religious aspects. This research employed a descriptive qualitative design within a positivistic paradigm. Data were collected through non-participant observation and semi-structured interviews with three elementary school children categorized into moderate, severe, and very severe addiction levels, along with parents as supporting informants. Data analysis followed the Miles, Huberman, and Saldana model, including data condensation, data display, and conclusion drawing and verification carried out simultaneously throughout the research process. The findings reveal significant differences in the frequency and duration of gadget use according to addiction levels. In the moderate category, children used gadgets for 1–2 hours per day, showing decreased concentration and mild emotional dependency. In the severe category, usage increased to 3–4 hours per day, accompanied by reduced social interaction, emotional control disturbances, and decreased learning motivation. In the very severe category, usage exceeded 5 hours per day, marked by social isolation, emotional regulation disorders, behavioral changes, and decreased discipline in learning and religious activities. These findings indicate that gadget addiction affects not only children’s psychological and social behavior but also the formation of moral and spiritual values. The study highlights the importance of parental supervision and proportional guidance in children’s gadget use.